5-Aminopyrazole as precursor in design and synthesis of fused pyrazoloazines - Ranjana Aggarwal; Suresh Kumar (Beilstein Journal of Organic Chemistry, 2018)
The condensation of 5-aminopyrazole with various bielectrophilic moieties results in the formation of pyrazoloazines, an interesting array of fused heterocyclic systems. The development of new synthetic routes towards pyrazoloazines for their biological and medicinal exploration is an attractive area for researchers throughout the world. The present review focuses on various synthetic methods developed in the last decade for the synthesis of differently substituted pyrazoloazines by a broad range of organic reactions by means of 5-aminopyrazole as a precursor.